Programs prerequisite of HACCP system for the cleaning procedure in restaurant - Moskalchuk, Olexandr; Kuzmin, Oleg; Stukalska (Ivanova), Nataliia (My University, 2022)
The purpose of the work is to implement the HACCP system when creating a prerequisite program for cleaning rooms and other surfaces in the restaurant business. Мета роботи – впровадження системи НАССР при створенні програми передумови прибирання приміщень та інших поверхонь у ресторанному бізнесі.
Keywords: кафедра технології ресторанної і аюрведичної продукції; HACCP; prerequisites program; room cleaning procedure; restaurant; програма передумов; процедура прибирання приміщень; ресторан